(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The complexes of the type MLCl¬2, where M = Co(II), Cu(II), Ni(II), Zn(II), Cd(II) and Hg(II) and L is the Benzofuran ligands derived from reaction between benzofuran-2-carboxyhydrazide and trimethoxyphenylmethine [BTMeOPMC] and nitrophenylmethine carbohydrazone [BNPMC]. All the complexes were characterized on the bases of elemental analysis, conductance, magnetic susceptibility measurements, UV-Vis, IR, 1H NMR, ESR spectra studies and X-ray data studies. Benzofuran ligands behave as bidentate by coordinating through the oxygen of the carbonyl group and the nitrogen of the hydrazide residue. Based on the results, we have proposed the probable structures for all the metal complexes. Both the ligands and their complexes have been screened for their fungicidal and bactericidal activities